Depolarization studies on low-depolarizing Cu/Ti and Ni(Mo)/Ti neutron supermirrors - Gómez-Guzmán, Jose Manuel; Bernert, Karina; Devishvili, Anton; Klauser, Christine; Märkisch, Bastian; Schmidt, Ulrich; Soldner, Torsten (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
Neutron supermirrors are a crucial part of many scattering and particle physics experiments. So far, Ni(Mo)/Ti supermirrors have been used in experiments that require to transport a polarized neutron beam due to their lower saturation magnetization compared to Ni/Ti supermirrors. However, next generation β decay experiments require supermirrors that depolarize below 10−4 per reflection to reach their targeted precision. The depolarization of a polarized neutron beam due to reflection off Ni(Mo)/Ti supermirrors has not yet been measured to that precision. Recently, Cu/Ti supermirrors with a lower saturation magnetization compared to Ni(Mo)/Ti have been developed, and may serve as an alternative. In this paper, we test the performance of both mirrors. At a first stage, we present four-states polarized neutron reflectivity curves of Ni(Mo) and Cu monolayers and m=2 Ni(Mo)/Ti and Cu/Ti supermirrors measured at the neutron reflectometer SuperADAM and perform a full polarization analysis, with the aim to extract information about their magnetic moment. The results found, however, were inconclusive, since it seems a detection limit of this method for all measured samples was reached. At a second stage, we measured the depolarization (D) that a polarized neutron beam suffers after reflection off the same Ni(Mo)/Ti and Cu/Ti supermirrors by using the Opaque Test Bench setup. We find upper limits for the depolarization of DCu/Ti(4N5)<7.6×10−5, DNi(Mo)/Ti<8.5×10−5, and DCu/Ti(2N6)<6.0×10−5 at the 1σ confidence level, where (4N5) corresponds to a Ti purity of 99.995% and (2N6) to 99.6%. These results show that all three supermirrors are suitable for being used in next generation β decay experiments. We found no noticeable dependence of the depolarization on the q value or the magnetizing field, in which the samples were placed.